Cryopreservation of Ovarian Tissue in Pediatric Patients - R. Fabbri; R. Vicenti; M. Macciocca; G. Pasquinelli; M. Lima; I. Parazza; V. Magnani; S. Venturoli (Hindawi Limited, 2012)
Cancer treatments improve the survival rate of children and adolescents; however chemo- and radiotherapy result in gonadal damage leading to acute ovarian failure and sterility. Ovarian tissue cryopreservation allows long-term storage of primordial follicles and represents the only possibility of preserving the potential fertility in prepubertal girls. The aim of the present study is to describe our experience in ovarian tissue cryopreservation in 45 pediatric patients. The number of follicles per square millimeter of the overall section area and follicle quality were evaluated histologically. A strong negative correlation was found between age and follicular density in patients both prior to and after chemotherapy (𝑃<0.0001). Damage in follicular quality, that is, increased oocyte vacuolization and detachment of the oocyte from granulosa cells, was found after chemotherapy. Ovarian tissue cryopreservation, preferably performed before initiation of chemotherapy, should be offered to pediatric patients, including prepubertal girls, at risk of sterility.